On the possibility of implementing Judicial Cooperation in criminal matters in the Andean Community: some lessons from the European Union and MERCOSUR - Zuñiga Schroder, Humberto (2023)
The Andean Community has as its ultimate goal the achievement of a common Latin American market, as stated in the Cartagena Agreement. To achieve this goal, in its more than fifty years of existence, various Decisions and Resolutions of supranational nature and mandatory compliance for its member countries have been issued on different matters; however, there are sectors in which there is still the need to regulate and strengthen cooperation ties. The purpose of this paper is to analyse the possibility of implementing judicial cooperation in criminal matters at the Andean level, taking various lessons learned from the European model and Mercosur; this in order to achieve deeper integration at the regional level.